Synchrotron radiation micro X‐ray fluorescence spectroscopy of thin structures in bone samples: comparison of confocal and color X‐ray camera setups. (9th December 2016) - Rauwolf, M.; Turyanskaya, A.; Roschger, A.; Prost, J.; Simon, R.; Scharf, O.; Radtke, M.; Schoonjans, T.; Guilherme Buzanich, A.; Klaushofer, K.; Wobrauschek, P.; Hofstaetter, J. G.; et al.
Abstract : To find the ideal synchrotron radiation induced imaging method for the investigation of trace element distributions in bone tissue, experiments with a scanning confocal micro X‐ray fluorescence system and a full‐field color X‐ray camera setup were performed. Abstract : In the quest for finding the ideal synchrotron‐radiation‐induced imaging method for the investigation of trace element distributions in human bone samples, experiments were performed using both a scanning confocal synchrotron radiation micro X‐ray fluorescence (SR‐µXRF) (FLUO beamline at ANKA) setup and a full‐field color X‐ray camera (BAMline at BESSY‐II) setup. As zinc is a trace element of special interest in bone, the setups were optimized for its detection. The setups were compared with respect to count rate, required measurement time and spatial resolution. It was demonstrated that the ideal method depends on the element of interest. Although for Ca (a major constituent of the bone with a low energy of 3.69 keV for its K α XRF line) the color X‐ray camera provided a higher resolution in the plane, for Zn (a trace element in bone) only the confocal SR‐µXRF setup was able to sufficiently image the distribution.